Current and future suitability of apis mellifera in Eastern and Southern Africa - Nenhowe, Samuel (BUSE, 2021)
Robust evidence underpinning the distribution of Apis mellifera races, their performance capacity and the adoption of Climate – Smart Apiculture (CSA) that fortifies Sustainable Developmental Goals linked (SDGs) to the four pillars of food and nutrition security and climate change being instrumental in poverty and hunger alleviation is currently lacking. In this study, the climatic and environment suitability to Apis mellifera races native in Africa, Asia, and America either managed or feral habitat, was investigated using Ecological Niche Modelling approach and associate geographical information system under current and future suitability the year 2050 and 2070. Two types of maps were extracted from spatial analysis, one for current ecological conditions and the second one for future suitability conditions. The study shows that most of Current and Future Suitability of Apis Mellifera in eastern and southern Africa is suitable for apiculture but more suitable areas are restricted to specific locations. In the future, environment suitability was found to be impacted by future climatic conditions mainly temperature and precipitation. Upper and eastern Sub-Saharan Africa will be impacted more than the middle or the far end of southern Africa. Apis mellifera relocation will be experienced especially at middle Sub-Saharan Africa map during 2070. It could be expected that Apis mellifera races could be distributed widely throughout eastern and southern Africa currently and in the future as well and in reclaimed ecologies. The spatial analysis was done using the major climatic factors that could impact Apis mellifera races distribution and productivities capacity namely maximum and minimum temperatures, precipitation and suitable environment in eastern and southern Africa. The honeybee plays a significant role as a keystone species to balance the ecological ecosystem, food sovereignty and climate change, conserve biodiversity through pollination services and bio indication. As a livelihood strategy, beekeeping improves resilient living standards thus effects of climate change are worthy to note. 13 bioclimatic variables sourced from WorldClim at 2.5 arc minutes were used for mapping the Apis mellifera races distributions. MaxEnt was employed to project distribution of the races under RCP 2.6 and RCP 8.5 for the years 2050 and 2070. The results showed substantial changes in the probability of occurrences when projected to 2050 and 2070 under the two RCPs, slight decrease in Apis mellifera races distribution across the eastern and southern Africa as well, erratic areas with probability of less than 0.2 were observed with no species occurrences. Whilst, Apis mellifera year 2070 projections observed a high expansion in habitat and encroachment of habitats with probability of occurrence above 0.5 was recorded however no races inhabitants were observed. There is need to practice biodiversity conservation and avoid overexploitation of forests especially in areas predicted to no longer have suitable habitats for the Apis mellifera races. Key Words: Beekeeping, Apis mellifera, Ecological Niche Modelling, Food Security, Climate Change.
Keywords: Apis Mellifera; Beekeeping; Ecological niche modelling